Ferroptosis: A novel cell death modality as a synergistic therapeutic strategy with photodynamic therapy - Yuqing Wang; Yiting Xu; Yong Qu; Yifang Jin; Juanmei Cao; Jinshan Zhan; Zhuoxia Li; Chuxing Chai; Changzheng Huang; Min Li (Photodiagnosis and Photodynamic Therapy)
Although there has been significant progress in current comprehensive anticancer treatments centered on surgery, postoperative recurrence and tumor metastasis still significantly affect both prognosis and quality of life of the patient. Hence, the development of precisely targeted tumor therapies and exploration of immunotherapy represent additional strategies for tumor treatment. Photodynamic therapy (PDT) is a relatively safe treatment modality that not only induces multiple modes of tumor cell death but also mediates the secondary immunological responses against tumor resistance and metastasis. Ferroptosis, an iron-dependent type of programmed cell death characterized by accumulation of reactive oxygen species and lipid peroxidation products to lethal levels, has emerged as an attractive target trigger for tumor therapies. Recent research has revealed a close association between PDT and ferroptosis, suggesting that combining ferroptosis inducers with PDT could strengthen their synergistic anti-tumor efficiency. Here in this review, we discuss the rationale for combining PDT with ferroptosis inducers and highlight the progress of single-molecule photosensitizers to induce ferroptosis, as well as the applications of photosensitizers combined with other therapeutic drugs for collaborative therapy. Furthermore, given the current research dilemma, we propose potential therapeutic strategies to advance the combined usage of PDT and ferroptosis inducers, providing the basis and guidelines for prospective clinical translation and research directionality with regard to PDT.